Pembelajaran Bangun Geometri Berbasis Kearifan Lokal Minangkabau: Studi Pustaka pada Struktur dan Simetri Rumah Gadang - Risky Winarta Naibaho; Saprina Marbun; Natalia Rama Kudadiri; Yesica P J A Siallagan; Nurhudayah Manjani; Kharismayanda Kharismayanda (STIKes Ibnu Sina Ajibarang, 2025)
Geometry learning at the elementary school level is often considered difficult and abstract by students due to the lack of connection with the context of everyday life. One innovative approach that can bridge this gap is ethnomathematics, which is mathematics learning based on local culture. This article is a literature study that aims to examine the structure and symmetry of Rumah Gadang as a representation of contextual geometry concepts in mathematics learning in elementary schools. Rumah Gadang, as a traditional house of the Minangkabau people, has an architectural form that is rich in geometric elements such as fold and rotation symmetry, flat shapes (triangles, trapezoids), transformations (rotation, translation, reflection), and spatial patterns and proportions. Through literature analysis from various scientific sources, it was found that the integration of geometric elements from Rumah Gadang into teaching materials such as RPP and LKPD was able to improve conceptual understanding, student learning interest, and strengthen cultural identity. This study confirms that the application of ethnomathematics not only enriches the learning experience contextually and meaningfully, but also supports the strengthening of values ​​in the Merdeka Curriculum and the formation of the Pancasila Student Profile.